THE LEGAL EFFECT OF ICJ ADVISORY OPINIONS REDEFINED? THE MAURITIUS/MALDIVES DELIMITATION CASE - JUDGMENT ON PRELIMINARY OBJECTIONS - Eichberger, Fabian Simon (Melbourne journal of international law, 2021)
The judgment contributed to the development of international law particularly by its progressive interpretation of the 'legal effect' of advisory opinions given by the International Court of Justice ('ICJ'). In 2010, it filed a claim against the United Kingdom under the United Nations Convention on the Law of the Sea (' UNCLOS'),7 arguing that the establishment of a Marine Protected Area (' MPA' ) around the Chagos Archipelago contravened UNCLOS. The Maldives based its argument on the Monetary Gold principle, according to which 'a court or tribunal cannot exercise its jurisdiction in the absence of an indispensable party'.20 Under this 'well-established procedural rule in international judicial proceedings',21 a judicial body lacks jurisdiction if the 'very subject-matter' of a decision would implicate the rights of a state that is not party to the proceeding.22 This, according to the Maldives, was the case for the United Kingdom because the Special Chamber would be required to rule on the sovereignty over the Chagos Archipelago to delimit the maritime boundary.23 In Mauritius' view, the Chagos Advisory Opinion of the ICJ had already determined in an 'authoritative' fashion that the United Kingdom possessed no sovereign rights regarding the Chagos Archipelago.24 Accordingly, the Special Chamber would not be required to determine the rights and obligations of the United Kingdom.25 The Special Chamber linked the discussion of the application of the Monetary Gold principle to the Maldives' second preliminary objection. Therein, the Maldives argued that the Special Chamber lacked jurisdiction over the dispute because 'a determination of Mauritius' claims would require this Tribunal to first determine whether it is Mauritius or the United Kingdom that has sovereignty over the Chagos Archipelago'.26 Relying on South China Sea Arbitration, Coastal State Rights in the Black Sea, Sea of Azov, and Kerch Strait and Chagos Marine Protected Area ('Chagos MPA Award), the Maldives emphasised that disputes over territorial sovereignty were not disputes 'concerning the interpretation of application of this Convention' under art 288(1) of the UNCLOS27 The Special Chamber considered these first two preliminary objections to run parallel to one another.